Differences in Graduation and Persistence Rates as a Function of Entry Requirements into Degree Programmes at Department Of Science Education, Federal University of Kashere - Ogundare, S. A.; Musa, , B. H. (Kashere Journal of Education, 2021)
This study examined the differences in graduation and persistence rates as a function of entry requirement into degree programmes at Department of Science Education, Federal University of Kashere, Gombe State. The study adopted a causal comparative design. The population of the study comprised all the one hundred and eleven (111) science education students from 2016 to 2018 academic session at Department of Science Education, Gombe State. All the 111 students in the department were purposively selected for the study because of the management size of the population and they were easily accessible. A structured questionnaire titled: Students’ Enrolment in Science Disciplines Questionnaire (SESDQ)was used for the collection of data from the participating students’ files. Data collected were analyzed with the used of descriptive statistics and Multivariate Analysis of Variance (MANOVA). The findings revealed that students with Direct Entry (DE) qualification had higher graduation rate than their counterparts UTME(SSEC/NECO) entry qualification. Conversely, Students with UTME entry qualifications had higher persistence rates than their colleagues with direct entry qualifications. The department should organize extramural coaching for UTME students and tutorials should be organized in the department, among other strategies that could help students to graduate and persistent in their university degree programmes at the stipulated time.